Sky Is Shooting Blue Arrows : Poems. - Luschei, Glenna (Mary Burritt Christiansen poetry series., 2014)
In this new book Glenna Luschei's poems take her and her readers around the world, including to Tunisia and Colombia, but in the end they return to center on the American West, where her heart lies. Celebrating life, travel, aging, and nature, this new book shines with Luschei's view of the world.